Evaluation of poultry by-products as a protein concentrate on the productive behavior in diets for laying japanese quail (Coturnix coturnix japonica) - Marchán Timorán, Andrea (2020)
The aim of this study was to evaluate the effect of the addition of the poultry feed by-product protein concentrate (CPSCA) to the quail laying diet on the productive performance and percentage of commercial eggs. The laying percentage, number of eggs per quail/period, average egg weight, feed consumption, feed conversion, egg mass, mortality, percentage of commercial eggs and economic retribution. A total of 108 female quails of 17 weeks of production were used in three experimental diets: T1 (0% inclusion of CPSCA, control); T2 (10% inclusion of CPSCA) and T3 (15% inclusion of CPSCA). The study lasted six weeks. The statistical model used was the completely randomized design with three treatments and three repetitions per treatment. There was no significant difference for the parameters under evaluation; however, the diet with 10% of the concentrate generated a higher economic return.